VALIDATION MODULE DEVELOPMENT ON WEBBASED CLASS DIAGRAM EDITOR - MICHAEL HASIAN - NIM: 13512092 , REINALDO
UML or Unified Modeling Language is a standard visual modeling language that is widely used in making software analysis and design models. Previously, UML diagram editors were created that allowed users to create and edit class diagrams (David, 2017). The diagram editor has automatic code generation features. But the diagram editor does not have a validator yet to check the validity of the resulting class diagram. In this Final Project a class diagram validation module is generated to complete the existing web-based class diagram editor. A validation module is needed to ensure the diagram class is valid so that the generated code framework is also valid. The existence of a validation module is also expected to be able to accelerate software development in the design stage by helping users detect invalid class diagrams so that the class diagrams can be immediately corrected. The class diagram representation in the diagram editor is an XML format mxGraph string variable. XML is extracted using XML DOM Parser to obtain class diagram elements. Furthermore, each element and linkages between elements are validated based on certain rules. The rules used are the UML diagram rules from StarUML. This module has not been able to validate semantically, but only do class diagram syntax validation. The validation module is built using the Javascript programming language. The methodology used in the construction of the validation module is iterative and incremental. This approach was chosen because the module construction was only carried out by one person and did not involve users, so there was no need for renewal requirements. The results achieved from this Final Project are validation modules that have been integrated into existing browser-based UML diagram editors. Based on the results of the test, a diagram editor that has been integrated with the validation module can check the validity of the class diagram created and display errors from the class diagram. Furthermore, this validation module can be further developed so that it can conduct semantic validation and validation is done in real time.